2020
DOI: 10.1080/09638180.2020.1760117
|View full text |Cite
|
Sign up to set email alerts
|

Political Uncertainty and Accounting Conservatism

Abstract: Political uncertainty leads to greater information asymmetry among contracting parties to the firm, resulting in an increased demand for accounting conservatism. Exploiting the exogenous variation in political uncertainty induced by the U.S. gubernatorial election cycle over the period 1963-2016, we find that the asymmetric timeliness of news recognition increases with political uncertainty. Our political uncertainty hypothesis operates through the contracting demand channel. Accordingly, we find that the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 80 publications
4
39
0
3
Order By: Relevance
“…We use Khan and Watt's () asymmetric timeliness measure because it provides a firm‐year measure of accounting conservatism with more variation than the traditional Basu () measure. Consistent with Dai and Ngo (), we also find that firms are more conservative during election years. Importantly, however, we find that our main results continue to hold after including the C score as an additional control variable interacting with the earnings variables, suggesting that our election dummy is not simply capturing differences in accounting conservatism.…”
Section: Primary Empirical Testssupporting
confidence: 90%
See 1 more Smart Citation
“…We use Khan and Watt's () asymmetric timeliness measure because it provides a firm‐year measure of accounting conservatism with more variation than the traditional Basu () measure. Consistent with Dai and Ngo (), we also find that firms are more conservative during election years. Importantly, however, we find that our main results continue to hold after including the C score as an additional control variable interacting with the earnings variables, suggesting that our election dummy is not simply capturing differences in accounting conservatism.…”
Section: Primary Empirical Testssupporting
confidence: 90%
“…An important feature of model (1) is that X t– 1 and X t also interact with the election year indicator, thus controlling for any systematic differences in earnings response coefficient during election years. Two recent studies provide evidence that managers make temporary changes in investment and accounting policies during election years (see, for example, Julio & Yook, ; and Dai & Ngo, ). The inclusion of the interactions between X t– 1 and X t and the election year indicator allows us to control for any actions that managers take during the election year that influence the nature of current period earnings.…”
Section: Empirical Method Data and Samplementioning
confidence: 99%
“…Dai and Ngo () examine the effect of political uncertainty on accounting conservatism, using a sample of 199 110 firm‐year observations between 1963 and 2016. They find that the asymmetric timeliness of news recognition in earnings increases in periods leading up to US gubernatorial elections because higher political uncertainty causes an increased contracting demand for accounting conservatism.…”
Section: Political Uncertainty and Corporate Policiesmentioning
confidence: 99%
“…Research has demonstrated that uncertainty increases the information asymmetry between firm internal management and information users. For example, high uncertainty increases firm debt costs, including bank loans and municipal bonds [3,22,42]; governor election inhibits the IPO of firms [43]; and general election encourages accounting conservatism [44,45]. In other words, reduced external explicit information produces negative agency cost benefit, and investors will reiterate requirements for high-quality information.…”
Section: For the Purpose Of Sustainability: Economic Policy Uncertainmentioning
confidence: 99%